Обеспечение сварки в магнитных полях - Лебедев, В. А. (Національний технічний університет "Харківський політехнічний інститут", 2004)
В статье, посвящённой проблемам защиты дугового механизированного оборудования от помехообразующего влияния внешних магнитных полей, предложено использовать экраны из магнитных материалов с дополнительным применением компенсирующего магнитного поля, образованного витками сварочного кабеля на магнитном экране.

The article is devoted to the problems of protection of the arc-mechanized equipment from influencing of external fields hindrances. It is recommended to use the compensating magnetic field created by the coils of welding cable on the magnetic screen. It is noted that impulsive influence on the transfer of electrode metal promotes stability of burning arc in the magnetic field, and in combination with magnetic screens can provide the high-quality conduct of welding. Expressions for estimation of magnetic screen parameters with the concrete example of its using are given.
Providing of welding in magnetic fields
Keywords: сварка; магнитное поле; дуговое механизированное оборудование; магнитный экран; welding; operating object; magnetic field; protection; magnetic screen; estimation; measuring